Proliferaciones algales nocivas de cianobacterias (Oscillatoriaceae) y dinoflagelados (Gymnodiniaceae) en el Golfo de Nicoya, Costa Rica - Vargas-Montero, Maribelle (2004)
Recently, the Pacific coast of Costa Rica has experienced an increase in both magnitude and frequency of harmful algae blooms (HAB). The lack of data regarding the dynamics of these events in the area, and the species of microalgae that produce them, are themes of great interest. The blooms have produced negative impacts on fishery resources and on human health in Costa Rica. In May 2002 a HAB left a large number of dead fish along the central Pacific coast. Water samples were collected using a phytoplankton net and fixed for subsequent processing by electron microscopy. In addition, a one liter sample of surface water was taken for later cell count. In the observed HAB, the dominating organisms found were the cyanobacteria Trichodesmiun erythraeum surrounded by high concentrations of Gram - bacteria and the dinoflagellate Cochlodinium cf. polykrikoides. T. erythraeum, is one of the most important N2 fixing cyanobacteria in marine waters that has been associated with HAB events in diverse parts of the world as well as with symptoms that produce contact dermatitis and other discomforts. C. cf. polykrikoides is a dinoflagellete associated with fish kills; although the type of associated toxins are unknown. In a national newspaper 17 cases of intoxication in humans were reported during this same period, which presented respiratory disorders and burning of the eyes. This is the first report in Costa Rica where a cyanobacteria and a dinoflagellate were observed together producing HAB.